Professional Gamer: The Meaning on Point Blank Online Play - Riauan, Muhd Ar. Imam; Aziz, Abdul (Universitas Semarang, 2019)
The growth rate of online game players in Indonesia is 33% average per year on 2010 and 35% on 2013. Majority of game players are not able to control game play activities and only waste time. On the other hand there is a group of online game players who are capable of achieving and succeeding in the online gaming world especially in playing Point Blank. This research use qualitative analysis with descriptive approach to investigate the professional online game player on Team Fun Group that consist of 6 player with different ability in Point Blank. This research show that the meaning on Point Blank give a chance for the playerto become professional gamers as long asthe players able to determine their goals and dreams in playing online games. Professional game playeralso must join a solid team to clear goal in play.